Otaria flavescens ... - Lucero, Sergio; Rodríguez, Sara M.; Teta, Pablo; Cassini, Guillermo; D'Elía, Guillermo (Zenodo, 2019)
Otaria flavescens (Shaw, 1800) Synonyms: aurita Bechstein, 1800; byronia de Blainville, 1820; chilensis Muller, 1841; chonotica Philippi, 1892; fulva Philippi, 1892; godeffroyi Peters, 1866; hookeri Schlater, 1866; leoninus F.G. Cuvier, 1827; minor Gray, 1874; molossina Lesson and Garnot, 1826; mollosinus Lesson, 1827; pernettyi Lesson, 1827; pygmaea Gray, 1874; rufa Philippi, 1892; ulloae Tschudi, 1844; uraniae Lesson, 1827; velutina Philippi, 1892. Neotype. MACN-Ma 23.26, Adult male, skull and mandible, almost without teeth, acquired by the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” on july 18th, 1923 (data on collector is missing) (Fig. 2). Type locality. San Sebastián (ca. -53.2979, -68.4512), Provincia de Tierra del Fuego, Antártida e Islas del Atlántico Sur, República Argentina (Fig. 3). Measurements of the neotype.- Condylobasal length = 346.4 mm; zygomatic width = 236.0 mm; braincase width = 120.5 mm; rostral length = 88.3 mm; rostral width = 100.0 mm; rostral height = 76.1 mm; ... : Published as part of Lucero, Sergio, Rodríguez, Sara M., Teta, Pablo, Cassini, Guillermo & D'Elía, Guillermo, 2019, Solving a long-standing nomenclatorial controversy: designation of a neotype for the southern sea lion Otaria flavescens (Shaw, 1800), pp. 296-300 in Zootaxa 4555 (2) on pages 297-299, DOI: 10.11646/zootaxa.4555.2.13, http://zenodo.org/record/2624283 ...